A bio‐available strontium isoscape for eastern Beringia: a tool for tracking landscape use of Pleistocene megafauna. (20th November 2020) - Funck, Juliette; Bataille, Clement; Rasic, Jeffrey; Wooller, Matthew
ABSTRACT: Numerous paleoecological questions concern the mobility of ancient fauna in eastern Beringia. Strontium (Sr) isotope ratio ( 87 Sr/ 86 Sr) analysis has emerged as a powerful tracer for determining the provenance of ancient biological materials. However, it is important to characterize 87 Sr/ 86 Sr variation across a landscape. We measured the 87 Sr/ 86 Sr composition of teeth from present‐day, herbivorous rodents ( n = 162) sampled from across eastern Beringia to estimate bio‐available 87 Sr/ 86 Sr values. We compiled these data with the very limited number of previously published 87 Sr/ 86 Sr values from the region. We then used this dataset and a machine learning, random‐forest regression to predict bio‐available 87 Sr/ 86 Sr variations across eastern Beringia. As a case study using our new 87 Sr/ 86 Sr map (isoscape), we measured the 87 Sr/ 86 Sr and oxygen stable isotope values (δ 18 O) of five radiocarbon‐dated steppe bison from eastern Beringia and compared these to our 87 Sr/ 86 Sr isoscape and a δ 18 O isoscape to estimate the probable landscape use of these ancient fauna. Our model and isoscape provide important foundations for a wide range of additional applications, including studies of the paleo‐mobility of other fauna, ancient people and present‐day fauna in eastern Beringia.